Listen, slowly - Lai, Thanhha (Harper, 2016)
After a back-breaking straight-A school year filled with too many extracurricular activities to count, twelve-year-old Mai's parents "reward" her by sending her to Vietnam, so she can get in touch with her roots. At first miserable, not knowing the language or customs, Mai spends time with her grandmother and learns to love her heritage, and even discovers secrets about her family's past, such as what happened to her grandfather during the war.